Survival analysis of single agent gemcitabine therapy in patients with metastatic breast cancer (Annals of Medical Research, 2021)
Aim: Gemcitabine has demonstrated experimental and clinical antitumor activity in various human neoplasms including pancreas, ovary, non-small cell lung and breast tumors. We aimed to investigate the factors affecting progression-free survival (PFS) and overall survival (OS) of patients who received single agent gemcitabine for metastatic breast cancer.Material Methods: Twenty-eight patients with metastatic breast cancer who were treated with gemcitabine in Gaziantep University Medical Faculty Medical Oncology Department between March 2007 and December 2018 were evaluated retrospectively. Gemcitabine 1000 mg / m2 was administered as a single agent treatment on the 1st and 8th days, every 21 days.Results: Twenty-seven (96.4%) of the patients were female and 1 (3.6%) was male. The median age was 52 years(range 35-76). Median PFS was 5 months (95% confidence interval 2,41-7,58) and median OS was 26 months (95% confidence interval 11,73-40,26). The median PFS of the patients with only lung metastasis was 16 months and the other patients were 4 months (Log-rank p = 0.020)Conclusion: Gemcitabine is a very well tolerated agent with sufficient efficacy for patients with metastatic breast cancer who were preferred to use single agent chemotherapy than combination therapies. Patients with only lung metastasis may benefit more from single agent gemcitabine in metastatic breast cancer.Keywords: Metastatic breast cancer; gemcitabine; progression-free survival; overall survival.
Keywords: Metastatic breast cancer; gemcitabine; progression-free survival; overall survival.